دور استخدام الطاقات المتجددة في التوجه نحو الاقتصاد الأخضر دراسة حالة الصين للفترة 1990-2018 - محمد السعيد, تواتي ابراهيم; بهاء الدين, مداني (University of eloued جامعة الوادي, 2020)
تهدف هذه الدراسة الى البحث في دور استخدام الطاقات المتجددة في التوجه نحو الاقتصاد الأخضر ضمن منهج وصفي تحليلي باستخدام جداول إحصائية ومواقع رسمية بالتطبيق على الصين،و قد تم تقسيم الدراسة الى فصلين تناول الفصل الاول ثلاث مباحث اولهم ماهية الطاقات المتجددة والتعرف عليها وثانيهم الاقتصاد الأخضر مفاهيم ومبادئ وثالثهم الدراسات السابقة حيث استطعنا من خلال هذا الفصل تقديم اهم المفاهيم والمقاييس لكلا من الطاقة المتجدد و الاقتصاد الأخضر في محاولة منا لفهم العلاقة بينهم وكيفية الوصول الى اقتصاد أكثر استدامة وتحقيق التنمية و من خلال اعتماد على الطاقة المتجددة بدلا من الطاقة الأحفورية الملوثة للبيئة ،ثم انتقلنا للفصل الثاني وهو محور الدراسة الخاصة بنا والقائم على مبحثين أولهما الاقتصاد الطاقوي في الصين وثانيهما الطاقات المتجددة في الصين ومدى تحقق الاقتصاد الأخضر لذلك حرصنا على النمو الأخضر لأنه يرجع بالاهتمام بالطاقات المتجددة للضغوط الناجمة عن تزايد الطلب الداخلي ،ومتطلبات حماية البيئة المتزايدة الصينية التي يجب التنوع في القطاعات الاقتصاد الأخضر من أجل الوصول الى استراتيجيات النمو الأخضر في الصين للتنمية للأجيال القادمة. This study amis to research the rôle of using renewable énergies in the direction of the green economy within a descriptive analytical approach using statistical tables and official websites in application to China, and the study was divided into two chapters. The first chapter dealt with three topics, the first of which is the nature of renewable energies and their identification and the second is the green economy concepts And the principles of the third and the prévois studies, where we were able through this chapter to present the most important concepts and standards for both renewable energy and green economy in an attempt to understand the relationship between them and how to reach a more sustainable economy and achieve development through relying on renewable energy instead of fossil energy polluting the environment, then We moved to the second chapter, which is the focus of our study, which is based on two topics, the first of which is the energy economy in China and the second is renewable energies in China and the extent to which the green economy has been achieved. Therefore, we have been keen on green growth because it is due to the interest in renewable energies due to the pressures resulting from the increase in internal demand, and the increasing Chinese environmental protection requirements that must be diversified In the green economy sectors in order to reach green growth strategies in the China for development for future generatio.
مذكرة مالية وتجارة دولية
Keywords: الاقتصاد الأخضر – الطاقة المتجددة – النمو الأخضر; green economy - renewable energy - green growth